2015
DOI: 10.1192/bjp.bp.114.147561
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve the experience of caring for people with severe mental illness: systematic review and meta-analysis

Abstract: Carer-focused interventions appear to improve the experience of caring and quality of life and reduce psychological distress of those caring for people with severe mental illness, and these benefits may be gained in first-episode psychosis. Interventions for carers should be considered as part of integrated services for people with severe mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
211
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(241 citation statements)
references
References 52 publications
(141 reference statements)
6
211
0
12
Order By: Relevance
“…37,38,40,41 Reviews addressing carers of people with various conditions at the end of life indicated studies of unclear quality, 42 mixed-quality studies 43 or studies at serious risk of bias, particularly in those focusing on carer outcomes. 44 Low-to moderate-quality primary studies were reported in one review 46 focusing on carers of people with mental health problems. 46 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…37,38,40,41 Reviews addressing carers of people with various conditions at the end of life indicated studies of unclear quality, 42 mixed-quality studies 43 or studies at serious risk of bias, particularly in those focusing on carer outcomes. 44 Low-to moderate-quality primary studies were reported in one review 46 focusing on carers of people with mental health problems. 46 …”
Section: Resultsmentioning
confidence: 99%
“…Of the reviews, 14 [19][20][21][22][23][24][25][26][27][28][29][30][31][32] focused on interventions for carers of people with dementia, four [33][34][35][36] focused on carers of people with cancer, four [37][38][39][40][41] focused on carers of people with stroke, three [42][43][44] focused on carers of people with various conditions at the end of life and two 45,46 focused on carers of people with mental health problems. Not all reviews reported the geographic location of the included primary studies.…”
Section: Overview Of the High-quality Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, therefore, cannot fulfill the role expected of individuals with chronic mental illness themselves, they have to take care of the family and support [1]. Patients often live with their parents at home.…”
mentioning
confidence: 99%